THE CONTRIBUTION OF WORK MOTIVATION AND COMMUNICATION TOWARD TEACHERS’ PERFORMANCE AT MUHAMMADIYAH 02 TANJUNG SARI MEDAN - Abdillah Abdillah; Ahmad Sulaiman (MANAGERE : Indonesian Journal of Educational Management, 2020)
The research aims to (1) reveal the work motivation teachers in SMA Muhammadiyah 02 Tj. Sari Medan, (2) reveal the teacher communication at SMA Muhammadiyah 02 Tj. Sari Medan, and (3) reveal the contribution of work motivation to the teachers’ performance in high school Muhammadiyah 02 Tj. Sari Medan. Sample withdrawal is done by probability sampling technique using total sampling method, with the number of samples used is 27 people. Data is collected using a Likert scale that has been tested with validation and its reabilitations. Data in analysis with simple regression techniques. The results of the first hypothesis analysis showed that the correlation coefficient between the work motivation variable (X1) and performance (Y) amounted to 0.263 thus the relationship is relatively weak. Meanwhile, based on the above summary of visible coefficient of determination (R2) obtained from the calculation of 0.069 which gives the meaning that the work motivation (X1) contributes to the contribution of 0.069 x 100% = 6.9% against performance (Y).